1996
DOI: 10.1177/000331979604700108
|View full text |Cite
|
Sign up to set email alerts
|

Inoue Balloon Pericardiotomy for Patients with Recurrent Pericardial Effusion

Abstract: The results and follow-up data for 11 patients with recurrent pericardial effusion due to various etiologies who underwent balloon pericardiotomy with the Inoue balloon catheter between May 1992 and July 1994 are described. Inoue balloon pericardiotomy was successful in 10 patients (91%), who remained free of pericardial effusion at a mean follow-up duration of 4.2 months. All patients tolerated the procedure well with minimal discomfort and with no complications. Despite good symptomatic relief, 9 patients (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 6 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…In their series of 42 patients, [Kopecky et al] reported the complication rate to be 2.4% and the recurrence rate to be 24%. In the study by [Chow et al], pericardial window formation via percutaneous balloon catheter was defined; however, sufficient experience has not yet been gained for the use of this method.…”
Section: Discussionmentioning
confidence: 99%
“…In their series of 42 patients, [Kopecky et al] reported the complication rate to be 2.4% and the recurrence rate to be 24%. In the study by [Chow et al], pericardial window formation via percutaneous balloon catheter was defined; however, sufficient experience has not yet been gained for the use of this method.…”
Section: Discussionmentioning
confidence: 99%
“…The technique is relatively simple, safe, and can be performed under local anesthesia and mild sedation, with minimal discomfort even in critically ill patients. Previous reports (14)(15)(16)18) described that the balloon should be inflated two to three times. For this procedure, we performed three inflations to ensure an adequate opening of the pericardium.…”
Section: Discussionmentioning
confidence: 99%
“…China is one of the biggest consumers of wild animals for food and traditional Chinese medicine in the world [48]. Although the origin of SARS-CoV-2 is still under debate, the initial cases were associated with the Huanan South China Seafood Market [49].…”
Section: Trafficking and Consumption Of Wild Animalsmentioning
confidence: 99%